Insulin-like growth factor I binding in hepatocytes from human liver, human hepatoma, and normal, regenerating, and fetal rat liver. - Caro, J F (1988)
Insulin-like growth factor-I (IGF-I) in human hepatoma cells (HEP-G2) has, in addition to its effect on cell growth, short-term metabolic effects acting through its own receptor. We have demonstrated that normal human hepatocytes, compared with HEP-G2 cells, have virtually no IGF-I binding sites. Because the rate of growth is the major difference between the hepatoma and the normal liver, we asked if normal liver might express IGF-I binding sites under physiologic growth conditions. Indeed, whereas adult rat hepatocytes have low IGF-I binding sites similar to those in human liver, hepatocytes from regenerating liver after 3 d subtotal hepatectomy have an approximately sixfold increase (P less than 0.005) and those from fetal rat liver a approximately 12-fold increase (P less than 0.005), to levels comparable to those in the HEP-G2 cells. The specificity of 125I IGF-I binding to its receptor was demonstrated by competition studies with monoclonal antibodies directed toward the IGF-I and the insulin receptors, with unlabeled IGF-I and insulin and by affinity labeling experiments. Thus, if IGF-I has any short-term metabolic functions in the adult human liver, it is not through interaction with its own receptor. Autocrine regulation by IGF-I of liver growth appears possible since IGF-I binding sites are expressed under pathological and physiological conditions of growth. The mechanism that couples these two phenomena remains to be elucidated.